EFISIENSI FAKTOR PRODUKSI PADA BUDIDAYA TAMBAK UDANG VANNAME DI DESA OENSULI KECAMATAN KABANGKA KABUPATEN MUNA - Wa Ode Angke; Budiyanto Budiyanto; Nurdiana Azis (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
Oensuli Village, Kabangka District of Muna  has the potential of  fisheries resource, particularly aquaculture shrimp. Until now, in the Oensuli Village there has been no information about efficiency in shrimp aquaculture. This study aims to determine the effect of input to output in shrimp ponds, and determine the efficiency of use of production inputs in the production process the shrimp ponds. Thirty five sample of businesses shrimp farming is determined by simple random sampling method. Data analysed with double linear regression and price efficiency. The results showed that the shrimp farming in the Oensuli village, fry, feed, and labor are positive significant effect on production, lime also significantly affect production but it is negative. While the influence of drugs do not significantly affect production. The conclusion from this research that the shrimp farming in the Oensuli village, fries and feed have not been efficient so need additional input, while lime and labor in-efficient in the production of shrimp, so the need to reduce the use of these inputs